PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KOMPETENSI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Sita Dewi; Ronaldo Sarco; Dwi Listyowati; Diana Setyo Dewi; Kuncu Saragih (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The retail sector in Indonesia is growing rapidly and is highly competitive; one example is Miniso, which operates 88 stores. To survive and more develope, businesses must improve their performance and productivity. Employees, as the company’s most valuable asset, are the driving force behind achieving high productivity, thereby ensuring the company’s goals are met. Factors that influence work productivity include work motivation, work discipline, and work competence. These three factors are fundamental elements that require serious attention from management. Work motivation is an internal or external drive that makes individuals more enthusiastic and innovative in their work, thereby increasing work productivity. Work discipline reflects an individual’s commitment and sense of responsibility in performing their duties. With strong discipline, employee performance improves, work quality increases, and productivity rises as a result. Job competencies refer to the abilities possessed by employees in the form of knowledge, skills, and work attitudes. Competencies are a key determinant of the quality of an employee’s work; strong competencies lead to strong performance, which in turn results in high productivity. This study aims to determine the influence of work motivation, work discipline, and work competence on employee performance. This study is a case study of Miniso employees at Central Park Mall in West Jakarta, with a sample size of 30 employees. The results show that, individually, work motivation, work discipline, and work competence significantly influence the work productivity of Miniso Central Park employees. Simultaneously, work motivation, work discipline, and work competence also influence the work productivity of Miniso Central Park employees.